Valuation considerations of stock based compensation: a case study of semiconductor firms - Engel, Russell; Lyons, Bridget (Journal of Accounting and Finance, 2025)
Equity research analysts and investors remain divided on the treatment of stock-based compensation (SBC) in firm valuation, particularly in discounted cash flow (DCF) and earnings multiples techniques. Many firms and analysts exclude SBC, viewing it as a non-cash expense, while others argue this leads to overvaluation. SBC usage is especially high in the tech sector. This study examines five large semiconductor firms, analyzing SBC levels, its treatment in adjusted earnings, and its impact on share dilution, valuation multiples, and free cash flow calculations. Findings indicate that SBC treatment significantly affects valuation, particularly within the semiconductor industry.
Keywords: Accounting; Actuarial science; Business; Econometrics; Economics; Engineering; Finance; Financial economics; Stock (firearms); Stock options; Valuation (finance); dept.acc

Generalist CEOs and operational efficiency - Chung, Hanyong (Finance research letters, 2025)
Keywords: Accounting; Board of directors; Business; Economics; Firm size; Generalist CEO; Generalist and specialist species; Operational efficiency; dept.acc; peer-reviewed

Product market competition and disclosure deficiencies in different mandatory filing types: Evidence from SEC comment letters - Ahn, J.H.; Chung, H. (Research in International Business and Finance, 2025)
Using firms’ receipt of SEC comment letters, this study investigates their selection of mandatory filing types when producing deficient disclosures in response to the product market competition. Empirical evidence reveals a positive association between two firm-level measures of product market competition and a firm's likelihood of receiving comment letters for non-10-K filings. These patterns are particularly pronounced when firms face a higher likelihood of new market entrants or operate as industry followers. Additionally, firms receiving comment letters for non-10-K filings experience increased sales and market share in the subsequent year. Overall, these findings suggest that firms strategically make deficient disclosures in non-10-K filings to minimize regulatory costs. © 2024 Elsevier B.V.
Keywords: Disclosure deficiency; Mandatory disclosure; Product market competition; Proprietary cost; SEC comment letters; dept.acc; peer-reviewed